Developing a Magic Pocket Game to Introduce Religious and Moral Values to 5-6 Year Old Children - Bety Fatqur Rohmah; Leli Fertiliana Dea; Isnaini Nur Azizah; Jauharotun Nafisah (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
Games are essential activities for early childhood because they provide enjoyable learning experiences. This study aims to develop and test the effectiveness of the